Preferensi dan tanggap fungsional Neoseiulus californicus McGregor (Acari: Phytoseiidae) sebagai predator Tetranychus kanzawai Kishida (Acari: Tetranychidae) - Sugeng Santoso; Edwin Iswella (Jurnal Entomologi Indonesia, 2013)
Kanzawa spider mite (KSM), Tetranychus kanzawai Kishida (Acari: Tetranychidae) is an important pest on many crops in Indonesia. Generally, farmers use acaricide to control this mite, which may cause negative side effects. One of the alternative control methods is the use of predatory mite. This research was done to determine prey preference and functional response of predatory mite Neoseiulus californicus (Acari: Phytoseiidae) on several life stages of KSM. Experiments were conducted under laboratory conditions. N. californicus were supplied with nymphs and adults of KSM to know its preference. N. californicus were also supplied with KSM eggs at several densities to know its functional response. Adult females and deutonymphs of N. californicus preferred KSM eggs than nymphs as their prey. The number of eggs consumed by adult females and deutonymphs N. californicus increased with the increase of prey density. The number of eggs laid by adult females of N. californicus increased with the increase of prey density. Searching time of the predator became faster with the increase of prey density. N. californicus showed cannibalism under low density of prey.